The Way of St. James: food consumption patterns of pilgrims - Monteiro, Rafael (2021)
The Way of St. James is in full growth in Portugal, and the pilgrimage route along the Portuguese North Coast has aroused the interest of several tourist agents. The city of Porto is the location chosen by most pilgrims to start this route. The aim of this study is to know the pilgrims' eating habits along the Way of St. James and its economic impact on the territory. A quantitative methodology was used and a questionnaire about the pilgrims' eating habits was applied regarding three different moments of the day - Breakfast, Lunch and Dinner, in three pilgrim hostels (”albergues") of the Way (Porto, Vila do Conde and Caminha) and in a F&B spot. The convenience sample consists of 225 individuals aged between 18 and 73, 70.2% being female. 36.9% of respondents are German and 86.22% are European. 50% of the respondents have a university degree and 61.8% are Christian. The study shows that pilgrims seek to enrich their gastronomic culture by consuming local products. Despite preferring carbohydrate-rich foods with high protein levels, they also worry about eating healthy and choosing vegetarian food. At the beginning and end of each stage, the pilgrims usually ask the Albergue's host for information about spots close to the accommodation, whenever they need to eat. During each stage, they are guided by a pilgrim guidebook, they ask local people and follow street advertising, rarely distancing themselves from the Way. The results show that, on average, pilgrims spend €4.53 on breakfast, €6.46 on lunch and €9.57 on dinner. The total average daily expenditure is estimated at €31.08, meals included. We can conclude that the average daily expenditure of the pilgrims is low, and that the amount spent on food represents about 2/3 of the total average expenditure, emphasising the importance of this topic. According to the sample collected, the pilgrims' food consumption has little impact on local economies. Considering the growing demand for this route, F&B businesses could take advantage of this study‘s findings to increasing their turnover.